Sistem Pengendali dan Monitoring Peralatan Listrik Rumah Tangga Melalui Web - Pranata, Mega; Andrasto, Tatyantoro (Jurusan Teknik Elektro Universitas Negeri Semarang, 2016)
Homecoming practice in Indonesia is done by most residents of the city to go back to their hometown. When they go their house empty and uncontrolled. The entire electronics equipment condition will be the same as the last condition until the owner returned. The purpose of this research is to create a system capable of controlling and monitoring electronic equipment well . This research use research and development method. With this method will be developed remote control system. The system will use arduino microcontroller and combined with web-based programming. This system will be tested by comparing the data sent and received by the system in accordance with the actual situation. The collected data will be used as the data for calculating the reliability of the system. This system will be used to control multiple lights, water pumps and read the high of water level .with This remote system all the lights and the water pump can be read in real that is turned on or off well, and can change the condition. The water level can be readed well. Data in real conditions, which are read in microcontroller Arduino and readable by the system have the same value. It can be concluded that the developed system has a good performance.